Application of ethnobotanical repellents and acaricides in prevention, control and management of livestock ticks: A review - Pavela, Roman; Canale, Angelo; Mehlhorn, Heinz; Benelli, Giovanni (Research in veterinary science, 2016)
Ticks transmit at least the same number or even more pathogens than any other group of blood-feeding arthropods worldwide affecting humans and animals. The eco-friendly control and management of tick vectors in a constantly changing environment is a crucial challenge. Besides the development of vaccines against ticks, IPM practices aimed at reducing tick interactions with livestock, emerging pheromone-based control tools, and few biological control agents, the extensive employment of acaricides and tick repellents still remain the most effective and ready-to-use strategies. However, the former is limited by the development of growing resistances as well as environmental concerns. Exploiting plants and plant products as sources of effective tick repellents and acaricides represents a promising strategy. In this scenario, the preservation of ethnobotanical information on repellent and acaricidal potential of plants is crucial. Here, we evaluated relevant information published in recent years, focused on plants used as repellents and acaricides against tick vectors in different regions worldwide. We selected a total of 238 plant species, which are traditionally used against ticks by native and local communities of Africa (Kenya, Uganda, Zimbabwe, South Africa), Europe (Serbia, Macedonia, Romania), Asia (Pakistan, India) and America (Brazil, Canada), from 56 families. However, only 7 families (i.e. Asteraceae, Euphorbiaceae, Fabaceae, Lamiaceae, Meliaceae, Apocynaceae and Solanaceae) represent the major quote (46%) of all plant species. We evaluated the differences in acaricidal and repellent efficacy of different formulations used. In the final section, implications arising from the surveyed anti-tick ethnobotanical knowledge and challenges for its future are discussed.
Keywords: repelenty proti hmyzu; Acaricides; Icaridin; Animals; Livestock; DEET; klíšťata; zvířata; akaricidy; Ticks; Argasidae; Lyme disease; Tick Infestations; Rickettsiales; dobytek; infestace klíšťaty; Ixodidae; Insect Repellents